(untitled) (International Journal of Food and Nutritional Sciences, 2021)
In India, both men and women got equal rights. However, this is only one side of the picture. In theory and before the law, men and women are equal but in practice women were subjected to all sorts of discrimination. Women struggle for their sheer survival. Friedrich Engels, in his work, The Origin of the Family, Private Property, and the State (1884) attempted to locate the subordination of women to the genesis of private property. Men hunted, fished, provided the raw materials for food and made the tools necessary to do works. Women cared for the house, prepared food, clothing and looked after the children. They were both masters in their field of activity. Whatever was produced was shared equally among the members of the house. As wealth started to accumulate, the relationship between men and women also changed. Since production became the more important than the administration of the household, the power of women began to wane. And women became necessary slaves, the new labour force.